Navigating the Regulatory Framework for HIV Prevention Research in Adolescents - Moore, Quianta; Bakhiet, Zeinab (The Journal of law, medicine & ethics, 2020)
Approximately 21% of new HIV diagnoses occurred in young people aged 13–24.1 87% of youth diagnosed with HIV were young men, and the vast majority of these infections were attributed to male-to-male sexual contact (93%).2 Creating a shared understanding of how to legally and ethically conduct research with adolescents is a key step to reducing the incidence of HIV in youth. While the ethics of including minors, without parental consent, in HIV prevention research is a very important consideration, IRBs have to first decide what is possible under the law. Different regulations apply to the type of research contemplated. Research studies regulated by the Federal Policy for the Protection of Human Subjects (the “Common Rule”) typically require parental permission for studies of minors, but allow waiver of parental permission if certain conditions are met.3 The Department of Health and Human Service (HHS) research regulations comply with the Common Rule and are codified in 45 CFR § 46.4 The Food, Drug and Cosmetic Act regulates all clinical investigations that support applications for research or marketing permits for products regulated by the Food and Drug Administration (FDA), including drugs and medical devices, and is more restrictive than the Common Rule.5 It is important to note that when research studies are regulated by both the FDA and the Common Rule — as is the case for most clinical pharmacological studies — the more stringent regulations govern. Other types of research, such as behavioral or educational interventions, would not be regulated by the FDA.The FDA does not permit waiver of parental permission for research involving children.6 The FDA regulation defines children as, “persons who have not attained the legal age for consent to treatments or procedures involved in clinical investigations, under the applicable law of the jurisdiction in which the clinical investigation will be conducted.”7 Thus, adolescents could only participate in FDA-regulated research if: 1) parental permission was obtained; or 2) the adolescent could legally consent to the intervention under the law of the state where research is being conducted, and therefore would not be considered a child (parental permission would not be required).In this issue of JLME, Bauman et al. recognize that there are several reasons why parental permission is important in protecting the rights of adolescents in research.8 However, there are a variety of justified rationales for not wanting to obtain parental permission as part of an FDA-regulated trial. For example, there could be public health justifications for not desiring parental permission.9 High-risk adolescents may avoid seeking services if parental permission is required or experience negative consequences from parents. Access to pharmacological therapies as part of a comprehensive HIV prevention strategy may be the key to protecting young men who have sex with men (MSM) and other high-risk adolescents from acquiring HIV,10 and not requiring parental permission may be an important component of ensuring equitable access to research for at-risk populations and optimizing research results.